2019
DOI: 10.3390/jcm8070935
|View full text |Cite
|
Sign up to set email alerts
|

Management of Glucose Control in Noncritically Ill, Hospitalized Patients Receiving Parenteral and/or Enteral Nutrition: A Systematic Review

Abstract: Hyperglycemia is a common occurrence in hospitalized patients receiving parenteral and/or enteral nutrition. Although there are several approaches to manage hyperglycemia, there is no consensus on the best practice. We systematically searched PubMed, Embase, Cochrane Central, and ClinicalTrials.gov to identify records (published or registered between April 1999 and April 2019) investigating strategies to manage glucose control in adults receiving parenteral and/or enteral nutrition whilst hospitalized in noncr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…In the medical nutrition setting, nutritional enteral formula for people with diabetes (Diabetes-Specific Formula: DSF) are available, aiming at limiting glycemic peaks and variability. Systematic reviews and meta-analyses in non-critically ill patients have indicated that DSF may improve hyperglycemia and glucose excursions in patients with T2DM [164,165]. It should be pointed out that no demonstration of improved hard outcomes, including mortality, is available, and that evidence does not include sufficient rigorous randomized controlled studies [164,165].…”
Section: Hospitalized Persons With Obesity With Covid-19 Withmentioning
confidence: 99%
“…In the medical nutrition setting, nutritional enteral formula for people with diabetes (Diabetes-Specific Formula: DSF) are available, aiming at limiting glycemic peaks and variability. Systematic reviews and meta-analyses in non-critically ill patients have indicated that DSF may improve hyperglycemia and glucose excursions in patients with T2DM [164,165]. It should be pointed out that no demonstration of improved hard outcomes, including mortality, is available, and that evidence does not include sufficient rigorous randomized controlled studies [164,165].…”
Section: Hospitalized Persons With Obesity With Covid-19 Withmentioning
confidence: 99%
“…The initiation of a nutritional therapy in complex clinical situations and its proper documentation are also tasks of an NST [69]. An NST ensures the quality and safety of nutritional interventions, especially artificial nutrition, which helps to reduce potential mechanical and metabolic complications (e.g., blood glucose issues and refeeding syndrome) as well as infections [70]. The NST has a consultative role for the treating medical staff in the hospital and takes over the management of the nutritional therapy in outpatients.…”
Section: Tasks and Challenges Of Nstsmentioning
confidence: 99%
“…Hyperglycemia is another early and frequent complication affecting up to 50% of the patients upon PN initiation. Appropriate and initially frequent glycaemia testing is mandatory, since hyperglycemia has been linked with increased morbidity and mortality, especially in critically ill patients [30]. The targeted blood glucose level lies between 7.8 and 10.0 mM, (normoglycemia: 4.4–8.1 mM; 80–145 mg/100 mL) [31].…”
Section: Complications Of Parenteral Nutritionmentioning
confidence: 99%
“…The targeted blood glucose level lies between 7.8 and 10.0 mM, (normoglycemia: 4.4–8.1 mM; 80–145 mg/100 mL) [31]. Insulin administration, optimally pump-assisted and in parallel to PN, may be necessary to control glycaemia (there is a dedicated specific article on this topic in this special issue [30]).…”
Section: Complications Of Parenteral Nutritionmentioning
confidence: 99%